Performance Evaluation of Linac Systems: Analysis of a Five-Year Quality Assurance (QA)/QC Data - Amoh, S.M. (University Of Ghana, 2018)
The main objective of radiotherapy is to increase therapeutic ratio (ratio of tumor control probability to the normal tissue complication probability) with minimal exposure to the personnel. In order to achieve this, the performance of the LINAC must be optimized to obtain the desired treatment result. The data collected on the equipment must be investigated retrospectively and extensively to assess the actual performance to check if it is functioning within the required standard. Quality Assurance helps to minimize errors and uncertainties in radiation therapy. Also with quality assurance errors can be detected and rectified sooner if they should occur. The objective of the study was to perform an in depth analysis on the quality assurance(QA)/ quality control (QC) data of LINACS(SB2, SB3, SB4 and SB6) over a five year operational period and to verify their performance against their acceptable limits. As part of this study new quality controls were measured to assess the current performance of the equipment and based on the risk assessment of the outcome some QA/QC data were analyzed on four LINACS (SB2, SB3, SB4, and SB6) over a five year operational period at St. Olav’s hospital in Norway. The results showed that all the deviations in the three directions (x, y and z) of the X-ray volumetric imaging (XVI) were within the tolerance limit of ±1 mm of SB2, SB3, and SB4 except for SB6 which recorded a mean deviation in 2015 that exceeded the tolerance limit by -0.01 cm, 0.12 cm and 0.1cm in the lateral(x), longitudinal (y) and vertical (z) directions respectively. In the absolute dose calibration measurements, the mean deviations were 0.149, -0.132, 0.013 and -0.400 % for SB2, SB3, SB4 and SB6 respectively for 6 MV whiles 15 MV produced mean deviations of 0.119, -0.059, -0.062 and -0.232% for SB2, SB3, SB4 and SB6 respectively. The absolute dose calibration readings of the LINACS (SB2, SB3, SB4 and SB6) were within the tolerance limit of ±0.5%.The mean deviations of Tissue Phantom Ratio (TPR) of SB2 were -0.040% and -0.110% for 6 MV and 15 MV respectively, and SB3 recorded mean deviations of -0.467% for 6 MV and -0.287% for 15 MV that fell within the limit of ±1%.The current deviations were 0.05% for 6 MV, -0.140% for 15 MV of SB2 and -0.560 and -0.01% for 6 and 15 MV respectively of SB3. The mean deviations in R50 of the electron energies were 0.200, 0.140, -0.180, -0.160 and -0.100 mm for 6 MeV, 8 MeV, 10 MeV 12 MeV and 15 MeV respectively which were within the tolerance limit of ±0.5 mm. The recent measurements of the electron energies showed deviations of 0.2, -0.3, -0.2, 0.3, and -0.3 for 6 MeV, 8 MeV, 10 MeV 12 MeV and 15 MeV respectively. The mean deviations in flatness, symmetry and fieldwidth of crossplane and inplane profiles of both electrons and photons were found to be in the tolerance limit of ±1%, ±1% and ±1mm (for 10 x 0 cm2 and 20 x 20 cm2 field size and ±2 mm for 40 x 40 cm2 field size) respectively.
MPhil.
Keywords: Linac Systems; Quality Assurance(QA); Quality Control (QC)